Transformative museum experiences / Licia Calvi, Arnold Vermeeren, Amalia Sabiescu, editors. - Calvi, Licia, 1968-; Vermeeren, Arnold; Sabiescu, Amalia (Springer series on cultural computing., 2026)
Following on from 'Museum Experience Design', this book acknowledges the changing role of museums in society with a focus on designing experiences as vehicles for transformation. We look at transformation through a systemic perspective, anchored in the experience that museums offer to visitors. One facet of our exploration regards the museum experience itself as an instrument for change. At this level we conceptualise what we mean by a transformative experience and look at design approaches specifically geared towards inducing transformation. We then turn attention towards the way recent changes in the socio-political and cultural context reverberated in structural and functional changes inside the museum and connected institutions and communities, with shifting museum identities and new forms of cooperation emerging.